Comparative study of therapist’s verbal behavior according its experience during clinical assessment - Froján Parga, María Xesús; Ruiz Sancho, Elena María; Montaño Fidalgo, Montserrat; Calero Elvira, Ana; Alpañés Freitag, Manuel (Anales de Psicología / Annals of Psychology, 2011)
The present study is an initial approach to the study of differ-ences between therapists with regard to their experience level. This type of study is based on the assumption that it is the expert therapist who does things well, and that the analysis of his/her behaviour will enable us to learn how to do therapy more efficiently. We used an observational meth-odology for the analysis of video-taped sessions. Verbal behaviour was coded with a coding system created for that purpose. Results show that the Discriminative, Reinforcement and “Others” functions were the most used by inexpert therapists, while Punishment, Elicitation, Motivating, Instructional, and Informative were the functions most used by expert therapists. Inter-mediate values were observed for most therapists with a middle degree of experience. Despite certain limitations, results indicate that there may be quantitative, as well as qualitative, differences with respect to what thera-pists do in session as a function of their experience level.